Case Report: Refractory macrophage activation syndrome requiring high-dose anakinra, emapalumab, and etoposide therapy in early-onset systemic juvenile idiopathic arthritis associated with adenoviremia - Slaney, Elizabeth D.; Modica, Renee; Woolnough, Leandra; Kafisheh, Dina; Bell-Brunson, Denise Heather; Elder, Melissa (Frontiers in Pediatrics, 2024)
Macrophage activation syndrome (MAS) is a life-threatening condition characterized by the excessive stimulation of macrophages and T lymphocytes, provoked by infections, malignancy, and autoimmune or autoinflammatory conditions like systemic juvenile idiopathic arthritis (sJIA). Clinical signs of sJIA may include high-spiking, quotidian fevers, lymphadenopathy, hepatosplenomegaly, and a salmon-colored migratory, evanescent rash. In contrast, MAS is characterized by unremitting fevers and diffuse, fixed, maculopapular rash. In addition to hepatosplenomegaly and lymphadenopathy; patients with MAS may also have clinical signs of coagulopathy, as well as cardiac, lung, renal, and central nervous system dysfunction. Empiric treatment for MAS is initially high-dose IV corticosteroids, but usually requires addition of immunomodulator such as tacrolimus or a biologic such as Anakinra to control. The addition of immunotherapies for MAS has improved patient outcomes. We present a two-year-old male patient with history of early-onset sJIA, who presented with MAS refractory to corticosteroids and anakinra triggered by adenoviremia that required addition of emapalumab to control. We believe this is the first reported case of combination immunosuppressive therapy of emapalumab, etoposide, anakinra, tacrolimus, and corticosteroids used in the successful treatment of infection-induced MAS in earlyonset sJIA. Given the lack of treatment guidelines and approved therapies for MAS, alternative strategies should be considered for patients with an intractable course.